Combined Anticancer Therapy for Prostate Cancer - Literature Review - Lasek, Patryk; Kowalczyk, Klaudia; Trąbka, Natalia; Lasota, Nina; Smerdzyński, Maciej; Łach, Katarzyna; Ściurka, Kinga; Demidowicz, Gabriela; Panuciak, Kinga; Kozicka, Karolina (Journal of Education, Health and Sport, 2024)
Prostate cancers represent a significant health problem, and their etiology is complex and multifaceted. It is estimated that in 2018, 1.3 million new cases and 359,000 deaths due to prostate cancer were diagnosed. They constitute the second most common group of cancers and the fifth most common cause of cancer-related deaths in men worldwide. The present study encompasses a literature review aimed at conducting an analysis of the potential of combined anticancer therapy as a prospective method for enhancing treatment efficacy, minimizing side effects, and improving long-term survival outcomes for prostate cancer patients. Combinations of compounds such as sunitinib with docetaxel, carboplatin with paclitaxel, estramustine or flutamide with luteinizing hormone-releasing hormone agonists, as well as docetaxel in conjunction with dexamethasone and octreotide, have demonstrated synergistic effects and an augmentation of therapeutic effectiveness. It is noteworthy to emphasize the potential enhancement of docetaxel's anticancer activity with concurrent administration of dexamethasone and octreotide, as well as combined therapy involving docetaxel, prednisone, and curcumin.